Guerreiro Ramos a Luta Contra o Racismo e a Descolonização da Brasilidade - Santos, Edson Bomfim dos (2021)
This research aims to demonstrate the structurality of racism in the Brazilian social thought, based on the socio-historical analises of the construction of our national identity, the political economic transformation and its consequences for the Brazilian black and mestizo population, during the period of greatest upheaval, which culminated in the process of consolidating national racism. We make a brief sociohistorical review that corroborates our thesis of the structurality of racism and we refer to the works of Alberto Guerreiro Ramos and his political and epistemological confrontation with racism, based on a project of socio-economic integration of the black element in the Brazilian society. By choosing Guerreiro Ramos as a reference for this debate, we highlight some aspects that significantly mark the Brazilian academic history. We emphasize that this choice can be justified by his condition as a black person. We add to it the look of our intellectuality on the black population (either anthropologically or culturally) and the influences of societal concepts and models transported from Western Europe and the United States, and, last but not least, the stage in which the development of sociology is in within our country. It is from this conjunctural framework that we see the structurality of racism, the role of the struggles developed by black organizations, the role of the State in the perpetuation of racism, as well as the role conceptual translations, already denounced specifically by Guerreiro Ramos in his work ―The sociological reduction‖ have on the maintenance and persistence of racism in the Brazilian society.